Cloning of the Plasma Membrane Sodium/Hydrogen Antiporter SOS1 for its Over expression in Rice - Razzaque, Samsad; Elias, Sabrina M.; Biswas, Sudip; Haque, Taslima; Seraj, Zeba I. (Plant Tissue Culture and Biotechnology, 2014)
Soil salinity adversely affects plant growth, development and disturbs intracellular ion homeostasis which results in cellular toxicity. The salt overly sensitive 1 (SOS1) gene is a critical component of salt tolerance in many species and encodes a plasma membrane Na+/H+ antiporter that plays an important role in germination and growth in saline environments. In the current study, the coding sequence of SOS1 gene (3447 bp) was amplified from a Bangladeshi rice landrace, Pokkali, by applying the fusion PCR strategy. SOS1 PCR amplicons were firstly cloned into pENTR/D-TOPO and then recombined with the binary vector, pH7WG2, through LR reaction. Positive colonies were validated by PCR, restriction digestion and sequencing. Finally, the constructed vector was transformed into Agrobacterium tumeficiens, LBA4404 strain, to initiate Agrobacterium-mediated transformation with the provision to transfer the cloned SOS1 into farmer popular rice varieties. D. O. I. http://dx.doi.org/10.3329/ptcb.v23i2.17527 Plant Tissue Cult. & Biotech. 23(2): 263-273, 2013 (December)